STUDY APPLICATIONS IN FINANCIAL FIELDS: AN ANALYTICAL REVIEW OF TOOLS AND TRENDS - Omonova Dilnoza Farkhod kizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In recent years, the intersection of data science, artificial intelligence, and financial analytics has led to the development of sophisticated study applications that support decision-making in the financial sector. This paper provides an in-depth review of study applications used in financial fields such as investment analysis, risk management, personal finance, and financial forecasting. Using a qualitative and comparative research method, this study explores the most widely used financial tools, evaluates their algorithms and features, and analyzes their impact on financial decision-making. The findings highlight the increasing importance of AI-driven and cloud-based financial applications and suggest future areas of development. The study also discusses the challenges such as data privacy, algorithmic bias, and over-reliance on automation.